The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.3390/polym14204265
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan-Hydroxyapatite Bio-Based Composite in Film Form: Synthesis and Application in Wastewater

Abstract: Water purification from toxic metals was the main objective of this work. A composite in film form was prepared from the biomaterials hydroxyapatite, chitosan and glycerol using the dissolution/recrystallization method. A nanoparticle-based film with a homogenous and smooth surface was produced. The results of total reflectance infrared spectroscopy (ATR-FTIR) and thermal gravimetric analysis (TGA/DTA) demonstrated the presence of a substantial physical force between composite components. The composite was tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The pseudo-second-order model was best suited to the Pb(II) adsorption data, indicating that the Pb(II) adsorption rate-limiting step is chemisorption via the exchange or/and sharing of the electrons between the metal ions and PS/AlOOH, surface chelation, or ion-exchange. Similar Pb(II) adsorption behavior was also reported on allophane [26] and polystyrene microplastics adsorbent [18].…”
Section: Effect Of Solution Phsupporting
confidence: 82%
See 1 more Smart Citation
“…The pseudo-second-order model was best suited to the Pb(II) adsorption data, indicating that the Pb(II) adsorption rate-limiting step is chemisorption via the exchange or/and sharing of the electrons between the metal ions and PS/AlOOH, surface chelation, or ion-exchange. Similar Pb(II) adsorption behavior was also reported on allophane [26] and polystyrene microplastics adsorbent [18].…”
Section: Effect Of Solution Phsupporting
confidence: 82%
“…The results in Figure 7 show that the adsorption of Pb(II) onto PS/AlOOH was fast during the initial few minutes due to the empty adsorption sites on the hybrid polymer. The active sites become occupied with the Pb(II) ions as the interaction time increases, and the complete saturation of PS/AlOOH active sites occurred in 90 min, indicating the equilibrium establishment and that no place would remain vacant on the PS/AlOOH [26].…”
Section: Adsorption Kineticsmentioning
confidence: 99%
“…It is also used in the food industry as a thickener, gelling agent, emulsifier, and stabilizer. It is mainly used in fruit juices, jellies, and jams, in cooking fruit preparations, fruit drink concentrates, desserts, dairy products, and delicatessen products [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a recent publication showed that pectin extracted from banana peels can be used as a mediator in the preparation of Hydroxyapatite (HAp) [Ca 10 (PO 4 ) 6 (OH) 2 ] nanoparticles [ 14 ]. Pectin can be also used to synthetize copolymers based on chitosan and/or HAp [ 8 ].…”
Section: Introductionmentioning
confidence: 99%